Self-Regulated Learning in the Tarbawi Interpretation Perspective and Its Implications for the Professionalism of Islamic Boarding School Management - Mifta Ghina Dzakiya; Hafid Muslih; Cecep Anwar; Muhammad Fahri Ali Husaeni; Wifa Fakhriyah Latifah; Moch Silmi Abdillah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The professionalism of administrators at the Nurul Iman Cibaduyut Islamic Boarding School is often hampered by the dilemma of dual roles between academic demands and administrative responsibilities, which has implications for burnout and suboptimal performance. This study aims to analyze the concept of Self-Regulated Learning (SRL) from the perspective of Tafsir Tarbawi and its implications for the professionalism of Islamic boarding school administrators. This study uses a qualitative approach with an integrative multidisciplinary design that synergizes Grounded Theory for field data with the Tafsir Maudhu'i method for analysis of the Qur'an text. The results of the study show that the concept of SRL in the perspective of tarbawi interpretation is divided into three theological dimensions, namely the planning phase (Forethought) based on Niyyah and the vision of the hereafter (QS. Al-Hasyr: 18), the implementation phase (Performance) based on Itqan and Muraqabah (QS. At-Taubah: 105), and the evaluation phase (Self-Reflection) based on Muhasabah (QS. Al-Qiyamah: 14). These values manifest into a 5C professionalism model: Commitment, Competence, Creativity, Control, and Consistency. This study concludes that the professionalism of Islamic boarding school administrators is not merely a technical achievement, but a manifestation of spiritual integrity built through a strong self-regulation mechanism.